Long-term outcomes of light chain amyloidosis patients receiving heart transplant: A single-center experience - Khush Patel, MD; Zoe H. Tu, PharmD; Carrie Yuen, MD; Siddhartha Ganguly, MD; Allison N. Yun, PharmD, BCTXP; Janardhana R. Gorthi, MD, MBBS; Barry H. Trachtenberg, MD; Ashrith Guha, MD, MPH; Mahwash Kassi, MD; Ju Kim, MD; Rayan Yousefzai, MD; Kelty Baker, MD; et al. (JHLT Open)
Background: Cardiac amyloidosis is a less common indication for orthotopic heart transplantation (OHT). Light chain (AL) amyloidosis specifically poses challenges. While previous small studies have established the validity of OHT for AL amyloidosis, we present experience from a large contemporary series at a single center. Methods: This was a retrospective single-center study of patients receiving OHT between 2009 and 2023 at our institution. A data warehouse was curated from our electronic medical records and United Network for Organ Sharing databases. Univariable and multivariable analyses of donor and recipient characteristics were performed. Patients who received OHT after 2016 were active in our electronic medical record and hence AL-OHT patients after 2016 had granular details regarding immunosuppression, chemotherapy regimens, amyloidosis, and post-transplant-related outcomes within their first-year post-OHT. Results: Thirty-one patients received an OHT for cardiac AL while 595 received OHT for non-amyloid indication during the study period. One-, three-, five-, and eight-year survival (87%, 83%, 73%, and 67%, respectively) was not statistically different compared to non-AL OHT patients (92%, 85%, 79%, and 68%, respectively). In a subset of 18 patients with access to electronic medical record data, all patients remained on tacrolimus and prednisone through 1-year post-OHT, but nearly half were off mycophenolate. Conclusion: Select AL patients with advanced cardiac involvement can gain survival advantage with OHT similar to other advanced heart failure patients.